ACTIVITY OF HETEROTROPHIC BACTERIA ISOLATED FROM MASJID RIVER, DUMAI, AGAINST PATHOGENIC BACTERIA - Zhilalul Huda; Feliatra Feliatra; Nursyirwani Nursyirwani (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT Heterotrophic bacteria is a group of organism that play important role in biogeochemical processes in aquatic ecosystem.The bacteria are able to decompose and remineralize organic materials into a simple inorganic components which is turn to nutrients for phytoplankton, perifiton, and other aquatic microflora. This Study was conducted from September to October 2018. The purpose of this study wos to obtain bacterial isolates that can be used as an antibacterial against pathogenic bacteria and to identify bacteria found in River estuary Masjid Dumai of Riau Province. Based DNA character the result found10 bacterial isolates. The bacterial (1A, 1B, 1C, 1D, 1E, 1F,1J, 2C, 2D, and 2G). These bacteria were able to inhibit the pathogenic growth. DNA identification using PCR and 16S rRN sequence technique resulting found6 types of bacteria, namely Bacillus cereus strain ATCC 14579, B. anthracis strain ATCC 14578 16S,B. methylotrophicus strain CBMB205 16S, B. thuringensis strain YBT-1518, B. pseudomycoides strainNBRC, and B. anthracis strain C10.Keywords: Heterotrophic Bacteria, Antibacteria, 16S rRNA Sequence, Pathogens.